EHSM: a conceptual ecohydrological model for daily streamflow simulation. Issue 9 (8th June 2013) - Viola, F.; Pumo, D.; Noto, L. V.
Abstract A parsimonious conceptual lumped model is here presented with the aim of simulating daily streamflow in semi‐arid areas. The model, processing daily rainfall and reference evapotranspiration at basin scale, reproduces surface and subsurface runoff, soil moisture dynamics, and actual evapotranspiration fluxes. The key elements of this numerical model are the soil bucket, where rainfall, evapotranspiration, and leakage drive soil moisture dynamics, and two linear reservoirs working in parallel with different characteristic response times. The surface reservoir, able to simulate the fast response of the basin, is fed by rain falling on impervious area and by runoff generated with excess of saturation mechanism, whereas the deep reservoir, which simulates the slow response, is fed by instantaneous leakage pulses coming from the soil bucket. Seven model parameters, which summarize soil, vegetation, and hydrological catchment properties, are assessed on a Sicilian basin, first using simple basic ecohydrological knowledge and then Monte Carlo simulations as well. The proposed model provides reliable estimate of daily runoff, accurate reproduction of flow duration curve, and physically consistent traces of soil moisture and evapotranspiration fluxes. Model performances are comparable in the two cases of calibrated and ecohydrologically driven parameters, emphasizing how basic descriptors are able to provide runoff estimation. Copyright © 2013 John Wiley & Sons, Ltd.